(untitled) (Contemporary Mathematics, 2024)
The object of this paper is to bring out the space rqB(g,p) of non-absolute patterns. Also, we will structure its completeness property. Also, the Köthe duals will be determined. Moreover, the Schauder basis for it will be constructed.